Turn-taking in collaborative storytelling: Et puis après (‘and then after that’) as a resource for resuming tellings-in-progress and negotiating tellership between story episodes - Dressel, Dennis (Linguistik Online, 2021)
This conversation-analytic paper investigates the multimodal design and interactional functions of the connective et puis après (‘and then after that’) in a French-language corpus of video-recorded collaborative storytellings. Two similar, yet different, sequential positions are investigated: the juncture between subsequent story episodes and the space between extended side sequences and the return to the story-in-progress. Such juncture positions constitute recognizable moments at which both members of the telling party, i. e., the current teller and the co-teller, must determine the topic of the next story episode as well as its delivery. Thus, juncture positions provide a perspicuous setting for the analysis of how tellership is negotiated and how topic progression is achieved. The connective et puis après appears to be a resource for current tellers to establish spaces for coparticipation at juncture positions, closing prior talk and projecting continuation. The multimodal analysis shows that both its prosodic design and co-occurring changes of the embodied participation framework contribute to opening interactive turn spaces and to making telling-specific next actions relevant.